Analisis Materi Ajar Konsep Laju Reaksi Pada Buku Teks Kimia SMA/MA - Sakti Sakti; Abdul Hadjranul Fatah; Maya Erliza Anggraeni (Jurnal Ilmiah Kanderang Tingang, 2020)
This study aims to: (1) describe the appropriateness of the concept of reaction rates in class XI high school chemistry teaching material against the 2013 curriculum, (2) describe the macro structure in class XI high school / MA chemistry teaching material on the concept of reaction rate, and (3) describe any propositions that are potentially misconceptions contained in class XI SMA / MA chemistry teaching material on the concept of reaction rate. This research is a type of descriptive research. The objects of this study are: (1) SMA / MA grade XI chemistry textbooks. The data obtained were analyzed descriptively. Macro discourse arrangement of reaction rate in text book A discussion of the concept of elaboration dimension reaches level 4 and the progression dimension there are 4 concepts at level 2. Macro structure discourse of reaction rate in text book B discussion of the concept of elaboration dimension reaches level 4 and the progression dimension there are 5 concepts at level 2. Propositions that have the potential for misconceptions in textbook A are the catalyst explanation and reaction rate constants. Propositions that have the potential for concept errors in textbook B are molarity formulas, writing the reaction coefficient, explanation of the influence of surface area, explanation of the reaction order 0, reaction order 1, reaction order 2, reaction order 2, reaction order -2, and reaction order ½.